Considerations on Burnout Syndrome in College Students - Mora, Paula (2024)
College students are suffering from Burnout. First, the loss of family and personal ties, due to the transfer of students from their places of origin to the university, is a social variable that serves as a catalyst. Second, college students may have some undeveloped executive functions; which becomes an internal factor that reinforces burnout; as the student fails to manage his or her time and tasks efficiently. And additionally, burnout can alter executive functions. Third, the two years of virtuality have provided students with experiences of flexible instructional styles that require less investment in time and money issues, which may be destabilizing individuals; who now find traditional learning styles more rigid and inefficient. Faced with all the problems presented, students develop strategies of a productive nature or focused on resolving the situation, followed by the search for social support and as a last strategy, non-productive or avoidance strategies; which clearly make your problem worse.